Utility of ripple mapping for identification of slow conduction channels during ventricular tachycardia ablation in the setting of arrhythmogenic right ventricular cardiomyopathy. (6th January 2019) - Xie, Shuanglun; Kubala, Maciej; Liang, Jackson J.; Yang, Jiandu; Desjardins, Benoit; Santangeli, Pasquale; van der Geest, Rob J.; Schaller, Robert; Riley, Michael; Supple, Gregory; Frankel, David S.; Callans, David; et al.
Abstract: Background: Ripple mapping displays every deflection of a bipolar electrogram and enables the visualization of conduction channels (RMCC) within postinfarction ventricular scar to guide ventricular tachycardia (VT) ablation. The utility of RMCC identification for facilitation of VT ablation in the setting of arrhythmogenic right ventricular cardiomyopathy (ARVC) has not been described. Objective: We sought to (a) identify the slow conduction channels in the endocardial/epicardial scar by ripple mapping and (b) retrospectively analyze whether the elimination of RMCC is associated with improved VT‐free survival, in ARVC patients. Methods: High‐density right ventricular endocardial and epicardial electrograms were collected using the CARTO 3 system in sinus rhythm or ventricular pacing and reviewed for RMCC. Low‐voltage zones and abnormal myocardium in the epicardium were identified by using standardized late‐gadolinium–enhanced (LGE) magnetic resonance imaging (MRI) signal intensity (SI) z ‐scores. Results: A cohort of 20 ARVC patients that had undergone simultaneous high‐density right ventricular endocardial and epicardial electrogram mapping was identified (age 44 ± 13 years). Epicardial scar, defined as bipolar voltage less than 1.0 mV, occupied 47.6% (interquartile range [IQR], 30.9‐63.7) of the total epicardial surface area and was larger than endocardial scar, defined as bipolar voltage less than 1.5 mV, which occupied 11.2% (IQR, 4.2 ± 17.8) of the endocardium ( P < 0.01). A median 1.5 RMCC, defined as continuous corridors of sequential late activation within scar, were identified per patient (IQR, 1‐3), most of which were epicardial. The median ratio of RMCC ablated was 1 (IQR, 0.6‐1). During a median follow‐up of 44 months (IQR, 11‐49), the ratio of RMCC ablated was associated with freedom from recurrent VT (hazard ratio, 0.01; P = 0.049). Among nine patients with adequate MRI, 73% of RMCC were localized in LGE regions, 24% were adjacent to an area with LGE, and 3% were in regions without LGE. Conclusion: Slow conduction channels within endocardial or epicardial ARVC scar were delineated clearly by ripple mapping and corresponded to critical isthmus sites during entrainment. Complete elimination of RMCC was associated with freedom from VT.